2008
DOI: 10.1111/j.1349-7006.2007.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β derived from bone matrix promotes cell proliferation of prostate cancer and osteoclast activation‐associated osteolysis in the bone microenvironment

Abstract: Metastatic prostate tumors in the bone microenvironment stimulate bone resorption, resulting in release of growth factors from the bone matrix that play important roles in tumor growth and osteoclast induction. Transforming growth factor β β β β (TGFβ β β β) is one of the most abundantly stored cytokines in bone matrix, regulating diverse biological activities. Here we evaluate its involvement in prostate tumor growth in the bone microenvironment, comparing with tumor growth in the subcutaneous microenvironmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…More importantly, we found that TGF-β could up-regulate the expression of RANKL, leading to the differentiation of osteoclasts. These results are also consistent with report from other investigator [31], suggesting that the activation of TGF-β, which is commonly seen in advanced PCa, could stimulate the differentiation of osteoclasts, leading to bone resorption and bone remodeling. Moreover, it is well known that TGF-β could also induce EMT [34], which facilitates PCa progression including invasion and bone metastasis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More importantly, we found that TGF-β could up-regulate the expression of RANKL, leading to the differentiation of osteoclasts. These results are also consistent with report from other investigator [31], suggesting that the activation of TGF-β, which is commonly seen in advanced PCa, could stimulate the differentiation of osteoclasts, leading to bone resorption and bone remodeling. Moreover, it is well known that TGF-β could also induce EMT [34], which facilitates PCa progression including invasion and bone metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, we found that isoflavone and BR-DIM could inhibit the differentiation of osteoclasts and osteoblasts when co-cultured with PCa cells, suggesting that isoflavone and BR-DIM would be useful for the inhibition of PCa bone metastasis and bone remodeling (Figure 8). It has been known that PCa cells in bone metastasis stimulate bone remodeling while bone remodeling facilitates PCa bone metastasis and invasion in the bone [29][31], which is known as a vicious cycle of bone remodeling and bone metastasis. Our results showed that isoflavone and BR-DIM inhibited bone cell differentiation, suggesting that isoflavone and BR-DIM could inhibit PCa bone metastasis through disrupting bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways regulating the function of bone remodeling have been reported in the past, including TNF-alpha/TNFR/TRAF1 and IL-6/CD126/JAK/STAT [30,31]. Osteoblast activity is strongly regulated by surrounding pH and growth factors released from resorbed bone matrix that stimulate osteoblasts to promote or inhibit bone formation [32,33]. This may have an impact on the bone mass outcome at each remodeling cycle [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways regulating the function of BMU have been reported in the past, including TNF-alpha/TNFR/TRAF1 and IL-6/CD126/JAK/STAT 40, 41. Furthermore, osteoblast activity is strongly regulated by surrounding pH and growth factors released from resorbed bone matrix that stimulate osteoblasts to promote or inhibit bone formation 42, 43. This may have an impact on the bone mass outcome at each remodeling cycle 44.…”
Section: Discussionmentioning
confidence: 99%